Sulfatides Primarily Exist in the Substantia Nigra Region of Mouse Brain Tissue. Issue 2 (11th January 2017) - Park, Kab‐Tae; Shon, Jong Cheol; Kim, Ji‐Eun; Park, Gyu Hwan; Choi, Hyun Jin; Liu, Kwang‐Hyeon
Abstract: Lipid distribution in the brain is important for many biological functions and has been associated with some brain diseases. The aim of this study was to investigate lipid distribution in different regions of brain tissue in mice. To this end, substantia nigra (SN), caudate putamen (CPu), hippocampus (Hip), hypothalamus (Hyp), and cortex (Cx) tissues of mice were analyzed using direct infusion nanoelectrospray‐ion trap mass spectrometry and multivariate analyses. The SN, CPu, Hip, Hyp, and Cx groups showed clear differences in lipid distribution using principal component analysis and a partial least‐squares discriminant analysis score plot, and lipid levels were significantly different in different brain regions. In particular, sulfatides were mainly distributed in the SN region. Our results could be used to help understand the functions and mechanisms of lipids in various brain diseases.